1984
DOI: 10.1111/j.1439-0434.1984.tb00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungistatic Activity of Essential Oils from Ocimum basilicum Chemotypes

Abstract: Essential Oils from Ocimum basilicum and their components showed different inhibition effects against Fusarium oxysporum f. sp. vasinfectum and Rhizopus nigricans, The different antifungal activity of the essential oils is determined mainly by the percentage of the main components: cineol, linalool, methylchavicol and eugenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…A atividade antifúngica dos óleos essenciais já está bem documentada, existindo estudos de seus efeitos em patógenos pós-colheita (REUVENI et al, 2008). As plantas medicinais e aromáticas como Mentha arvensis L. e Zingiber officinale R., contém princípios ativos antimicrobianos, que podem ser promissores para a conservação de flores de corte, pois atuam no controle de fungos fitopatogênicos, além de não afetarem o meio ambiente (TOSI et al, 1996).…”
Section: Introductionunclassified
“…A atividade antifúngica dos óleos essenciais já está bem documentada, existindo estudos de seus efeitos em patógenos pós-colheita (REUVENI et al, 2008). As plantas medicinais e aromáticas como Mentha arvensis L. e Zingiber officinale R., contém princípios ativos antimicrobianos, que podem ser promissores para a conservação de flores de corte, pois atuam no controle de fungos fitopatogênicos, além de não afetarem o meio ambiente (TOSI et al, 1996).…”
Section: Introductionunclassified
“…The findings of this study showed that using sweet basil in vitro inhibited Fusarium oxysporium spore germination, and the percentage inhibitory zone was substantially higher than the control. [28] examined the extent to which the primary basil ingredients suppressed F. oxysporum growth, they determined that against F. oxysporum, eugenol had the most enormous rate of suppression (100%) while linalol and methyl chavicol had 26.4 and 30.3%, respectively, of inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…9 (2022) Phytochemical analysis of Dianthus caryophyllus showed that it contained triterpenes, alkaloids, coumaruns, cyanogenic glycoside, cyanidin, pelargonidin, the yellow isosalipurposide, essential oil, volatile oil and many other chemical contents. Carnation, thyme and basil plants are source of aroma compounds and essential oils containing several biologically active constituents that possess insecticidal [11], nematicidal [12], fungistatic [13] and antimicrobial properties [14 , 15]. The potent antimicrobial ability is related to their essential oils content of high concentrations of eugenol, carvacrol and thymol [16].…”
Section: Introductionmentioning
confidence: 99%